ANTIBACTERIAL ACTIVITY OF SYNTHESIZED SILVER NANOPARTICLES BY SIMAROUBAGLAUCA AGAINST PATHOGENIC BACTERIA - CHANDRAPPA, C. P.; CHANDRASEKAR, N.; GOVINDAPPA, M.; SHANBHAG, CHAITRA; SINGH, UTTAM KUMAR; MASARGHAL, JAYASHRI (International Journal of Current Pharmaceutical Research, 2017)
Objective: The present study outline the plant-mediated synthesis of silver nanoparticles (AgNPs) using leaf extract Simaroubaglauca, which act as both reducing and stabilizing agent. Methods: Formation of silver nanoparticles was confirmed by primarily by Ultraviolet/visible spectroscopy. X-ray diffraction studies revealed the crystallinity of the nanoparticles. The scanning electron microscopy was carried out to determine the mean particle size, as well as the morphology of the NPs and the composition of elements, was studied with Energy Dispersive X-ray analysis (EDS). Results: The silver nanoparticles were spherical in shape with a mean size of 23 nm. The EDS showed strong optical absorption peak at 3keV and it was confirmed the formation of AgNPs. The synthesised AgNPs further utilized for the evaluation of antibacterial activity and shown significant antibacterial activity against Escherichia coli, Pseudomonas aeruginosa, Enterobacter and Klebsiella pneumonia at 50 Âµg/ml and 100Âµg/ml concentrations. Conclusion: The synthesised silver nanoparticles have been characterised by UV-vis, SEM-EDAX and XRD to determine the sizes and shapes of the silver nanoparticles.